1999
DOI: 10.1128/cdli.6.6.783-786.1999
|View full text |Cite
|
Sign up to set email alerts
|

Antibody to Human Endogenous Retrovirus Peptide in Urine of Human Immunodeficiency Virus Type 1-Positive Patients

Abstract: Human endogenous retrovirus (HERV)-like sequences are normal inherited elements that constitute several hundredths of the human genome. The expression of genes located within these elements can occur as a consequence of several different events, including persistent inflammation or genotoxic events. Antibodies to endogenous retroviral gene products have been found in a number of infectious, chronic, and malignant diseases, suggesting a role in disease initiation and progression. We studied human immunodeficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…It could be suggested that HPV infections might participate in endogenous retroviral reactivation through either a trans ‐complementation or a trans ‐activation process. In addition, RNA viruses such as human immunodeficiency virus (HIV) type 1 can reactivate expression of HERVs and promote an antibody response to them 36,37 . Such mechanisms could explain the occurrence and the severity of HIV‐associated psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…It could be suggested that HPV infections might participate in endogenous retroviral reactivation through either a trans ‐complementation or a trans ‐activation process. In addition, RNA viruses such as human immunodeficiency virus (HIV) type 1 can reactivate expression of HERVs and promote an antibody response to them 36,37 . Such mechanisms could explain the occurrence and the severity of HIV‐associated psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…Testing urine specimens of HIV-1 infected individuals and healthy controls for antibodies against a peptide derived from the gammaretrovirus HERV-E Env protein showed that 36.4% and 81.3% of patients in the CDC AIDS categories A and B/C respectively, contained specific antibodies, while none of the HIV-negative controls tested positive [ 77 ]. Fourteen peptides derived from various endogenous retroviruses were used to search for IgM and IgG antibodies in HIV-1 infected and uninfected immunosuppressed persons by Lawoko et al .…”
Section: Herv Proteins and Antibodies In Hiv Infected Patientsmentioning
confidence: 99%
“…Another approach to investigating interactions between HERV and HIV uses anti-HERV immune responses in HIV-1-infected individuals as a marker of HERV activation. Early reports found no differences between HIV-1-infected patients and healthy control groups with regard to anti-HERV Env or Gag antibodies (147,194,195), although others reported clear evidence for anti-HERV antibodies (187,(196)(197)(198). These conflicting results may have been due to the use of different antigens for screening or to the genetic backgrounds of the respective cohorts.…”
Section: Influence Of Other Viruses On Hml-2 Expressionmentioning
confidence: 97%